Salinity-induced modulations in sexual and asexual reproduction in the freshwater planarian Dugesia bursagrossa (nomen nudum species): Insights from microtubular cytoskeleton and oxidative stress marker analyses - Abdel Halim Harrath; Waleed Aldahmash; Lamjed Mansour; Khalid Elfaki; Saleh Alwasel (Journal of King Saud University: Science, 2024)
Global warming-induced environmental changes have resulted in salinity fluctuations that markedly impact aquatic organisms. Consequently, the salinization of freshwater has become a major concern. Among these organisms, planarians are highly sensitive to environmental changes, especially Dugesia bursagrossa, the first freshwater planarian species identified in Saudi Arabia, which reproduces both sexually and asexually through fission. This study examined the reproductive response of sexual and asexual D. bursagrossa specimens to salinity changes. Asexual reproduction rates were found to increase with elevated salinity, whereas sexual reproduction was sensitive to high salinity, evidenced by the absence of cocoons in treated groups. This phenomenon was further explored by investigating the microtubular cytoskeleton’s organization in the sexual form’s ovary using immunolabeled α-tubulin and confocal microscopy. Results revealed a significant decline in the tubulin cytoskeleton with rising salinity levels, supporting the notion that increased salinity restricts sexual reproduction. Given that heightened salinity induces stress, the activities of malondialdehyde (MDA) and various antioxidant indicators, including glutathione (GSH), superoxide dismutase (SOD), and catalase (CAT), were evaluated. Elevated salinity led to a notable increase in MDA levels as well as reduced GSH, SOD, and CAT levels in both sexual and asexual specimens, with sexual organisms exhibiting more pronounced effects. In conclusion, salinity directly impacts the homeostasis and reproduction of D. bursagrossa, with sexual specimens facing greater challenges than their asexual counterparts.